Segmental relaxations have macroscopic consequences in glassy polymer films - Chowdhury, Mithun; Freyberg, Paul; Ziebert, Falko; Yang, Arnold C.-M.; Steiner, Ullrich; Reiter, Günter (Physical review letters, 2012)
We have investigated the consequences of physical aging in thin spin-coated glassy polystyrene films through detailed dewetting studies. A simultaneous and equally fast exponential decay of dewetting velocity, width, and height of the rim with aging time was observed, which is related to a reduction of residual stresses within such films. The temperature dependence of these decay times followed an Arrhenius behavior, yielding an activation energy of 70±6 kJ/mol, on the same order of magnitude as values for the β-relaxation of polystyrene and for relaxations of surface topographical features. Our results suggest that rearrangements at the level of chain segments are sufficient to partially relax frozen-in out-of-equilibrium local chain conformations, i.e., the cause of residual stresses, and they might also be responsible for macroscopic relaxations at polymer surfaces.